GRIN2B mediates susceptibility to intelligence quotient and cognitive impairments in developmental dyslexia. (February 2015) - Mascheretti, Sara; Facoetti, Andrea; Giorda, Roberto; Beri, Silvana; Riva, Valentina; Trezzi, Vittoria; Cellino, Maria R.; Marino, Cecilia
<x xml:space="preserve">Abstract</x> Objective(s) Developmental dyslexia (DD) is a complex heritable condition associated with impairments in multiple neurocognitive domains. Substantial heritability has been reported for DD and related phenotypes, and candidate genes have been identified. Recently, a candidate gene for human cognitive processes, that is, GRIN2B, has been found to be associated significantly with working memory in a German DD sample. In this study, we explored the contribution of six GRIN2B markers to DD and key DD-related phenotypes by association analyses in a sample of Italian nuclear families. Moreover, we assessed potential gene-by-environment interactions on DD-related phenotypes. Materials and methods We carried out a family-based association study to determine whether the GRIN2B gene influences both DD as a categorical trait and its related cognitive traits in a large cohort of 466 Italian nuclear families ascertained through a proband affected by DD. Moreover, we tested the role of the selected GRIN2B markers and a set of commonly described environmental moderators using a test for G×E interaction in sib pair-based association analysis of quantitative traits in 178 Italian nuclear families. Results Evidence for a significant association was found with the categorical diagnosis of DD, performance intelligence quotient, phonemic elision, and auditory short-term memory. No significant gene-by-environment effects were found. Conclusion Our results add further evidence in support of GRIN2B contributing toward DD and deficits in DD. More specifically, our data support the view that GRIN2B influences DD as a categorical trait and its related quantitative phenotypes, thus shedding further light on the etiologic basis and the phenotypic complexity of this disorder.